Structure,microstructureandionicconductivityofthesolidsolution LiTi2 xSnx(PO4)3 - (:unkn) unknown (Université akli mohand oulhadj Bouira, 2011)
The NasiconcompoundswiththecompositionLiTi2 xSnx(PO4)3 (x¼0–1.8) weresynthesisedbythe solid statereaction.TheirstructuresweredeterminedfromX-raypowderdiffractionusingRietveld analysis.AllthecompositionspresentthespacegroupR-3c.TherefinementsshowthattheTiandSn cations arestatisticallydistributedoverthesamepositionwhiletheLionesareexclusivelylocatedon the M1site.Thelatticeconstants a and c exhibit linearvariationoverthewholecompositionrange.The bond lengthsareinaccordancewiththoseofotherNasiconstructures.TheSEMmicrographsofthe samplesshowrelativeporousmicrostructures.Theionicconductivityisabout10 4–10 5 S cm 1; for the activationenergy,atypicalvalueof0.32eVisobtainedfor x¼0.6 compositionwhereassignificant deviationfromlinearityinthetemperaturedependenceofthedcconductivity,isobservedfortheSn- rich ones.Thistendencyisdiscussedalongwiththestructuralfeatures
Keywords: Impedance spectroscopy, X-ray diffraction , Crystal structure ,Ionic conductivity , Microstructure